A Comprehensive Review of the Strategies to Reduce Retinoid-Induced Skin Irritation in Topical Formulation - Angga Cipta Narsa; Cecep Suhandi; Janifa Afidika; Salsabil Ghaliya; Khaled M. Elamin; Nasrul Wathoni (Hindawi Limited, 2024)
Currently, retinoids are known for their abundant benefits to skin health, ranging from reducing signs of aging and decreasing hyperpigmentation to treating acne. However, it cannot be denied that there are various side effects associated with the use of retinoids on the skin, one of which is irritation. Several approaches can be employed to minimize the irritation caused by retinoids. This review article discusses topical retinoid formulation technology strategies to reduce skin irritation effects. The methodology used in this study is a literature review of 21 reference journals. The sources used in compiling this review are from PubMed, Scopus, ScienceDirect, and MEDLINE. The findings obtained indicate that the following methods can be used to lessen retinoid-induced irritation in topical formulations: developing drug delivery systems in the formulation, such as encapsulating retinoids, transforming retinoids into nanoparticles, forming complexes (e.g., with cyclodextrin), and binding retinoids with carriers (e.g., polymers, NLC, SLN), adding ingredients with anti-irritation activity, skin barrier improvement, and increased skin hydration to retinoid formulations (e.g., combinations of glucosamine, trehalose, ectoine, sucralfate, omega-9, and 4-t-butylcyclohexanol, addition of ethanolic bark extract of Alstonia scholaris R. Br).